Pourquoi les incendies de forêts sont-ils si meurtriers? - Chevrou, Robert B. (EDP sciences, 2005)
This work propounds a description and an analysis of the phenomena that occur during forest fires. By providing technical explanations about all the phenomena, one by one, it enables firemen and everyone else, to understand, to act, to be prepared and to protect themselves against the dangers of these dramatic events.